Developing Anti-Corruption Society Through the Core Values of Surah Al-Fatihah and Its Implications for National Education - Taufikin, Taufikin; Sholihah, Hani; Nurhayati, Sri (Jurnal Pendidikan Agama Islam Al-Thariqah, 2025)
This study aims to explore the anti-corruption values in Surah Al-Fatihah and its implications for national education. Surah Al-Fatihah contains moral principles, such as honesty, integrity, justice, and trustworthiness, which can be the basis for character education in efforts to prevent corruption. This study uses a library research method by analyzing the interpretation of Al-Fatihah and literature related to anti-corruption education and Islamic values in the education system. The analysis is carried out through a textual and contextual approach to explore the meaning of Al-Fatihah verses and their relevance to the formation of individual characters with integrity. The results of the study show that the values in Surah Al-Fatihah can be integrated in education through the Islamic Religious Education (PAI) and Civic Education (PKn) curriculum. Case-based learning strategies and the creation of an integrity school ecosystem can also strengthen anti-corruption awareness from an early age.